(untitled) (Educação e Pesquisa, 2008)
The aim of this article is to think the problem of the teaching of philosophy from the perspective of the work of Deleuze and Guattari. These authors have created a series of concepts along their philosophical work to understand what it means to do philosophy, that is, to understand a philosophical activity that moves away from the reflection upon something, to be founded on an act of philosophical creation. According to them, there are four concepts that contribute to understand such philosophical work, namely Concept, Plane of Immanence, Conceptual Persona, and Problem. We assume that these concepts can be useful to think the contemporary teaching of philosophy in a way different from what has been the case. Special attention was given to one of these concepts, Plane of Immanence, developed in the last joint work of these authors, What is philosophy? (1997). We have sought in the work of these authors to understand how one can think the teaching of philosophy in such a way as to distance it from a conceptual fitting to a transcendent or transcendental, which according to the authors employed here would push the concept of teaching into a conceptual dogmatism. The proposal of this article is to seek a way out of this problem, thinking the teaching of philosophy based on the very immanence in which this teaching is produced.